Трематоды дальневосточной кефали-пиленгаса (Mugil soiuy) в Азовском море - Домнич, И.Ф.; Сарабеев, В.Л. (Вестник зоологии, 2000)
Фауна трематод дальневосточного пиленгаса, который был акклиматизирован и интродуцирован в Азовськом море, расширена на 18 видов. Отмечено 4 вида (Saccocoelium obesum, Saturnius papernai, Phagicola sinoecum mtc. и Mesorchis sp. 1 mtc.) известные для Черного моря, но в Азовском море ранее не встречавшиеся. Сделан общий анализ зараженности пиленгаса трематодами. Установлено, что ядро фауны включает в себя 9 видов: Acanthostomum imbutiforme mtc., Saccocoelium tensum, Diplostomum spp. mtc., Ph. sinoecum mtc., S. papernai, Lecithaster galeatus, Heterophyidae gen. sp. larvae, Pygidiopsis genata mtc., Posthodiplostomum brevicaudatum mtc. Среди них к потенциально патогенным для акклиматизированной кефали отнесены 2 вида: Acanthostomum imbutiforme mtc., Phagicola sinoecum mtc. В фауне трематод выделены 2 группы видов: специфичные паразиты местных кефалевых (8 видов: Haplosplanchnus pachysomus, S. obesum, S. tensum, Haploporus lateralis, Dicrogaster contracta, L. galeatus, S. papernai, Ph. sinoecum mtc.) и широко распространенные паразиты разных отрядов рыб, известные для Азово-Черноморского региона (11 видов: Bunocotyle cingulata, Mesorchis sp. 1 mtc., A. imbutiforme mtc., P. genata mtc., Cryptocotyle concavum mtc., Heterophyidae gen. sp. larvae, Diplostomum spathaceum mtc., D. rutili mtc., D. chromatophorum mtc., Tylodelphys clavata mtc., P. brevicaudatum mtc.). As a result of studying of the Far-East-pelingas which was introducted and acclimatized in the Azov Sea aquatories we’re discovered another 18 known species of trematodes that were found widespread in host fish. Among then 4 species: Saccocoelium obesum, Saturnius papernai, Phagicola sinoecum mtc. and Mesorchis sp. 1 mtc. were encountered in the Black Sea but never in the Azov Sea. We’re accomplished the general analysis of the infection of the pelingas by trematodes. We’re established that the main body of the fauna includes 9 species: Acanthostomum imbutiforme mtc., Saccocoelium tensum, Diplostomum spp. mtc., Ph. sinoecum mtc., S. papernai, Lecithaster galeatus, Heterophyidae gen. sp. larvae, Pygidiopsis genata mtc., Posthodiplostomum brevicaudatum mtc. 2 species out of this number have been found to be of pathogenic danger to the acclimatized mullet: A. imbutiforme mtc., Ph. sinoecum mtc. Were distinguished 2 groups of species within the fauna of trematodes: I. The specific parasites of the local mullets (8 species): Haplosplanchnus pachysomus, S. obesum, S. tensum, Haploporus lateralis, Dicrogaster contracta, L. galeatus, S. papernai Ph. sinoecum mtc. II. The widespread parasites beloning to different orders of fish known in the Azov-Black Sea region (11 species): Bunocotyle cingulata, Mesorchis sp. 1 mtc., A. imbutiforme mtc., P. genata mtc., Cryptocotyle concavum mtc., Heterophyidae gen. sp. larvae, Diplostomum spathaceum mtc., D. rutili mtc., D. chromatophorum mtc., Tylodelphys clavata mtc. P. brevicaudatum mtc.